Pressure‐Enhanced Superconductivity and Structural Phase Transition in Layered Sn4P3 - Hao Ding; Jingyu Hou; Kun Zhai; Xin Gao; Junquan Huang; Feng Ke; Bingchao Yang; Congpu Mu; Fusheng Wen; Jianyong Xiang; Bochong Wang; Tianyu Xue; et al. (Small Structures)
High pressure provides a unique tuning method depending on structure modulation to explore the structure–property relationship. Herein, the pressure‐induced structural phase transformation and enhanced superconductivity in a layered binary phosphide Sn4P3 are reported. Comprehensive measurements using in situ synchrotron X‐Ray diffraction and Raman spectroscopy reveal a structural phase transition with mild distortion of SnP3 building blocks and interlayer shrinkage under high pressure. This differs from a conventional trigonal SnAs(P)3 to square SnAs(P)4 topotactic transition in SnAs(P)‐based compound. Through this structure reconstruction under high pressure, electron distribution has been reorganized and phonons have softened, facilitating a high superconducting temperature (Tc) value of 7.8 K at 34.9 GPa, which is almost six times higher than its ambient value. The study introduces a new transition route in layered SnAs/SnP‐based intermetallic materials and provides insight into the structural and electronic changes under high pressure for Sn4P3.